COVID-19-related anxiety among dental students in two dental schools in Saudi Arabia - Mahmoud El Homossany; Ghada Sultan Alrowaily; Wysal Abdullah Allugmani; Waleed Khalid Abo-Atwan; Rafat Ayman Al-Sulaiman; Obayy Mohammed Al-Mofareh; Aseel Salem Alharbi; Abdulrahman Daher Almuqrin (Wolters Kluwer Medknow Publications, 2021)
Background: Dentistry can be an overstressed career. Dentists come across countless routes of stress in dental schools. Onset foot in clinical training, they can find that the number and type of stressors often grow. Dental students encounter high levels of academic stress, which can adversely influence them from their study years working with phantom teeth through their preclinical and clinical practice years. The COVID-19 pandemic has revealed the world population to a high risk of infection that comprises a major stress factor, especially for vulnerable groups such as dental students. Objective: The objective of this study was to assess the levels of COVID-19-related stress and anxiety, changes in hygienic and social habits, as well as subjective worries regarding the dental profession among dental students. Materials and Methods: A self-structured questionnaire was sent to dental students of two dental schools in the city of Jeddah. It included demographic data, questions about the level of change in personal hygiene and social habits, students' perception about the sufficiency of information received during the outbreak and its source, subjective worries regarding the dental profession, and the Generalized Anxiety Disorder 7-item Scale. Three hundred and eight responses were received. Results: Moderate and severe anxieties were reported in 41% and 7% of students, respectively. About 57% of respondents agreed to continue e-learning in the theoretical part only, 1% for the clinical part only, 32% in both, and 10% were not interested in continuing e-learning. Most of the students reported that they received excellent information about COVID-19 during the outbreak, with social media as the main source of information for the majority, followed by the Health Department. A significant number of dentists (66%) wanted to temporarily shut their dental practices until the number of COVID-19 case rates reduces considerably. Conclusion: A considerable percentage of dental students are anxious and changed their hygienic and social habits due to COVID-19. This anxiety reflects worries about the dental profession in one-third of participants that necessitate counseling services and psychological support.